Frugal Innovations in The Food Industry – The Possibilities for Implementation and The Direction of Future Research - Małgorzata JUCHNIEWICZ (Communications of International Proceedings, 2022)
Conducting innovative activity is a strategic element of the development of every enterprise. In recent years, it has also played a significant role in the food industry, which is referred to as a mature and slowly developing sector. The article discusses the concept of frugal innovation and the possibilities for food companies to implement it. Recommendations for the direction of future research in this area were also indicated.
Keywords: innovations; frugal innovations; food industry